Dimensions of organizational learning: contextual variables in companies under lean manufacturing implementation - Tortorella, Guilherme Luz (2014)
The Lean Production (LP) is an approach that encompasses a variety of management practices to reduce losses and improve operational efficiency. Due to this fact, the ability to innovate, change and learn continuously presents itself as a key element in the implementation of the LP. Several contextual variables were mentioned in the literature as potential impediments to implementing lean. However, little is known about the influence of these variables on the dimensions of Organizational Learning (OL). This study aims to examine the relationship between six contextual variables and the frequency of occurrence of problems in companies that are implementing the LP. Furthermore, the identification of relevant relationships between dimensions of OL and contextual variables contribute to the identification of the contexts in which problems can be expected to occur. The sample contains thirteen companies implementing the LP. The results indicate that the same contextual variables, which are deemed as influential to implement LP, have a different influence on the ability of organizational learning.